Combined impact of the cold vortex and atmospheric blocking on cold outbreaks over East Asia and the potential for short-range prediction of such occurrences. (1st August 2022) - Zhuo, Wenqin; Yao, Yao; Luo, Dehai; Simmonds, Ian; Huang, Fei
Abstract: This study explores the consequences of independent and combined effects of blockings on the northeast Asian cold vortex (NACV), and corresponding cold outbreaks over East Asia (EA) during boreal winters of 1979–2019. The results show that the development of NACV is closely associated with blocking over the Ural Mountains (UB) upstream and eastern Siberia to mid-North Pacific (SPB) downstream. Here we focus on the initial periods before the peak day of NACV events. It is found that the strong NACV events are usually induced by the initial-UB situation, leading to the greatest temperature drop in EA. While the weak NACV events may be associated with the initial-SPB condition, which can bring less dramatic outbreaks but longer duration, owing to the Ural ridge that formed by the westward shift of SPB. Furthermore, an SPB-UB relay effect is discovered against the background of a negative Arctic Oscillation pattern. In such cases, UB is formed by the westward shift of downstream SPB after the occurrence of NACV, forming a relay effect that motivates the second NACV process, hence prolonging the duration of cold anomalies in EA. These findings highlight the importance of the combined effect of blockings and NACV in the intraseasonal time scale. Compared to the 'Initial-UB' and 'Initial-SPB' situation, this 'SPB-UB relay' scenario can produce longer-lasting cold extreme in EA, which may be indicative of the short-term weather forecasting of such extreme cold weather.